2018
DOI: 10.4103/aam.aam_63_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ramadan fasting on glycemic control and other essential variables in diabetic patients

Abstract: Background: Fasting during the holy month of Ramadan is a religious obligation for all Muslims who represent 1.8 billion of the world population (24%). This study explores the effect of Ramadan fasting on the blood glucose, glycated hemoglobin (HbA1c), lipid profile, sleeping quality, and essential lifestyle parameters and also explores the safety of fasting for a whole month among diabetic patients. Aim: The aim of the present study was to assess the impact of Ramadan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…women [10,11,14], or a more chronic fasting (during Ramadan) model in 81 women [9,12,13,15]. In our assessment, the acute model is likely very similar to the interruption of caloric intake as part of analgo-sedation related to surgery or diagnostic interventions [1-3, 10,11,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…women [10,11,14], or a more chronic fasting (during Ramadan) model in 81 women [9,12,13,15]. In our assessment, the acute model is likely very similar to the interruption of caloric intake as part of analgo-sedation related to surgery or diagnostic interventions [1-3, 10,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] are useful for extrapolation as there is likely a major burden to conduct such studies in an immediate postoperative setting.…”
mentioning
confidence: 99%
“…Recent evidence indicated clear effect of Ramadan fasting on triglycerides level in diabetic patients. Bener et al [62] tried to investigate the effect of Ramadan fasting on some blood parameters including blood lipids (total cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, etc. )…”
Section: The Effect Of Ramadan Fasting On Triglyceridesmentioning
confidence: 99%
“…The Effect of Ramadan Fasting on Metabolic Syndrome (MetS) DOI: http://dx.doi.org /10.5772/intechopen.89333 in patients with type 2 diabetes mellitus (T2DM) in Turkey. They concluded that fasting during the month of Ramadan may help to reduce triglycerides level even in people with type 2 diabetes [62]. Interestingly, rare of the available evidences showed negative effect of Ramadan fasting on triglycerides concentration.…”
Section: The Effect Of Ramadan Fasting On Triglyceridesmentioning
confidence: 99%
See 1 more Smart Citation